Size-frequency and allometric growth of the yellowfin tuna, Thunnus albacares (Bonnaterre, 1788), caught in the Molluca Sea, Indonesia - Wahono, Budi; Lumingas, Lawrence J.L (Universitas Sam Ratulangi, 2013)
Yellowfin tuna Thunnus albacares (Bonnaterre, 1788) is a very important species for the world fisheries. Biological information including length-frequency distribution, total length (TL)-head circle length (HCL) relationship, and total length-body weight (BW) relationship were examined for 115 female and 84 male yellowfin tuna, caught in Molluca Sea. Significantly different mean total length was found for female and male yellowfin tuna; the male (mean length 110.66 cm) is bigger than the female (mean length 103.36 cm). The total length-head circle length relationship for female yellowfin tuna can be described as HCL= 0.7455TL0.9565 and HCL= 0.7821TL0.9456 for male yellowfin tuna. In the HCL-TL relationships, the allometric coefficient (b) values obtained for both female and male yellowfin tuna did not differ significantly from 1 or isometry, which indicates direct proportionality between HCL and TL. The estimated total length-body weight relationship for yellowfin tuna was BW = 0.0172TL2.9826 for female and BW = 0.0223TL2.9281 for male. In the BW-TL relationships, the allometric coefficient (b) values obtained for both female and male yellowfin tuna did not differ significantly from 3 or isometry, which indicates direct proportionality between BW and TL. This biological information will be useful for the fisheries management of the species studied.Â Ikan madidihang Thunnus albacares (Bonnaterre, 1788) merupakan spesies yang sangat penting untuk perikanan dunia. Informasi biologi yang meliputi sebaran frekuensi panjang, hubungan panjang total (PT)-panjang lingkar kepala (PLK), dan hubungan panjang total-berat tubuh (BT) telah diteliti untuk 115 individu ikan madidihang betina dan 84 individu ikan madidihang jantan yang tertangkap di Laut Maluku. Rata-rata panjang total ikan madidihang betina berbeda nyata dengan rata-rata panjang total ikan madidihang jantan; ikan madidihang jantan (110,66 cm) berukuran lebih besar dibanding ikan madidihang betina (103,36 cm). Hubungan panjang total-panjang lingkar kepala untuk ikan madidihang betina adalah PLK = 0,7455PT0,9565 dan untuk ikan madidihang jantan adalah PLK = 0,7821PT0,9456. Dalam hubungan PLK-PT, nilai-nilai koefisien allometri (b) untuk ikan madidihang betina dan jantan tidak berbeda nyata dengan 1 atau isometri, yang mengindikasikan pertumbuhan yang proporsional antara PLK dan PT baik untuk ikan betina maupun untuk ikan jantan. Hubungan panjang total-berat tubuh dugaan adalah BT = 0,0172PT2,9826 untuk ikan madidihang betina dan BT = 0,0223PT2,9281 untuk ikan madidihang jantan. Dalam hubungan BT-PT, nilai-nilai koefisien allometri (b) untuk ikan madidihang betina dan jantan tidak berbeda nyata dengan 3 atau isometri, yang mengindikasikan pertumbuhan yang proporsional antara BT dan PT baik untuk ikan betina maupun untuk ikan jantan.Â Informasi biologi ini akan berguna untuk pengelolaan perikanan dari spesies yang dipelajari.